Canons of linguistic knowlegde in textbooks for teaching technical English at an academic level - Haładewicz-Grzelak, Małgorzata; Dolińska, Magdalena (Scripta Neophilologica Posnaniensia, 2018)
Canons of linguistic knowlegde in textbooks for teaching technical English at an academic level